The Living Space of the Kazan Tatars as a Unique Phenomenon at the Turn of the 19-20 Centuries - Khakimovna Karamova, Klara; Radikovna Akhmetshina, Gulnaz; Fargatovich Usmanov, Salavat (International Journal of Criminology and Sociology, 2022)
The article considers the living space of Kazan as a unique phenomenon in the history of Tatar culture. The structural consistency of all the elements that can be united in a single ensemble, organically combining a utilitarian and spiritual function are the main feature. All elements of the estate complex are considered from the perspective of a general ideological concept. The period of development of Kazan Tatars housing at the turn of the XIX - beginning of XX centuries is covered. Separate ownership with a complex of buildings for residential and household purposes is considered, this period of development of the city coincides with the replacement of classic style by various eclectic styles. Beginning in 1917, the social revolution turned the history of architecture in a different direction, so this work was decided to limit this research range. The same time frame is limited to the main fund of preserved historical documents on the history of Tatar settlements. The nature and resources, the development of the region, the practical skills of the owner, his interests and spiritual needs, traditions in the family and in the region - these qualitative characteristics played a decisive role in the development and transformation of the living space of the Tatars. The identity of each apartment building was determined by a whole range of conditions, a new vision of the living environment in connection with the surrounding nature was established. The owner of the house sought to realize idea of ​​the perfect arrangement of the world in his small surrounding area, as well as in rituals and rules of conduct, ways of spending time and doing activities, the way of haking care the household, where all the elements of the arrangement obeyed the plan of the apartment building, they thought carefully over and the consequence was that there was nothing accidental. Connection, unity in the awareness of nature, social principles and religious beliefs are the main feature and uniqueness of the entire national Tatar way, spirituality, mentality. Inimitable and unique national Tatar space of a residential building can be considered the material form of this association.